ANALISIS GAYA BAHASA DALAM SLOGAN LINGKUNGAN HIDUP - nfn Marnetti (Balai Bahasa Provinsi Riau, 2017)
This study aims at describing kind of language styles and meaning that existed in environmental slogans by applying descriptive qualitative method. The data in this article were collected from one of website titled “Pengertian dan 100 Contoh Slogan Lingkungan Hidup Terbaik (Meaning and 100 Examples of The Best of Environtmental Slogan” (www.pribahasaindonesia.com). The collected data were analyzed by using the theory of diction and style of language and semanticsso the kind of language styles and the meaning contained in the slogan would be found. After being analyzed, the data are classified by the type of language style and meaning contained in the slogan. The results shows that there are 49 simple styles, 12 repetition styles, 6 parallelism styles, 1anastrof style, 3 assonance styles, 8 metonymy styles, 3 personification styles, 1 asindenton style, 3 spoken language styles, 3 eponym styles , 3 antithesis styles, 4 unofficial language styles and 1kiasmus styles. Meaning contained in the environmental slogan is 80 lexical meanings, 10 figurative meanings, 2 associative meanings and 2 illocutionary meaning. The most abundant language style in these slogans is a simple language style and some of the slogans use foreign terms.